Strategi Pembelajaran Daring Praktik Vokal di Prodi Musik Fakultas Seni Pertunjukan ISI Yogyakarta - Nugroho, Titis Setyono Adi; Kusumaningrum, Maria Regina Murti (Universitas Hamzanwadi, 2021)
The background of this study is based on the impact that occurred due to the Covid-19 pandemic that attacked the world including Indonesia, especially in the education sector which requires learning to be done online. In this case the impact specifically occurred on vocal practicum-based learning in the Music Study Program of the Faculty of Performing Arts, Yogyakarta Indonesian Institute of Arts. Human vocal sound as a learning priority becomes vulnerable to being distorted due to internet network instability, lack of bandwitdh and music facilities owned so that output becomes not maximal. The purpose of the research is to find out the right, effective and efficient online learning strategies in the vocal practice lectures of the Music Study Program of the Faculty of Performing Arts, Yogyakarta Indonesian Institute of Arts. As a theoretical foundation, the study used the concept of interaction by Belawati and the locus of control by Lowes and Lin. This research is qualitative with case study methods and uses purposive techniques, observations and interviews. The results of the study found that the interaction between lecturers in vocal practice, fostered students, vocal learning materials, and the learning system or technical used is a collection of elements that synergize with the attitude of personal reflection or locus of control in an effort to form an online learning strategy of appropriate, effective and efficient vocal practice in the Music Study Program of the Faculty of Performing Arts, Yogyakarta Indonesian Institute of Arts.